Bahasa Pergaulan Remaja: Analisis Fonologi (Dialek Sosial) Dalam Era Masa Kini - Dimas Prananda; Desy Rizky F; Nur Afidah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2023)
In phonological analysis in social media, the types of words found in adolescent promiscuous language tend to be short or short. These abbreviations occur in two processes, namely contraction and acronym. The formative thing in this case is how the form, using the phoneme on the suffix —in. Whereas phonological features found in adolescent promiscuous languages are the tendency to use vowels /e, o and/; pronounced sounds, declension, reinforcement, and vocal fusion